An overview on transesterification of natural oils and fats - Shahla, Sanaz; Ngoh, Gek Cheng; Yusoff, Rozita (Springer Verlag, 2010)
Transesterification of natural oils and fats has found various industrial applications, particularly in producing surfactants and biodiesel fuel. Due to the biodegradability and environmental compatibility of the products, many studies have been conducted in this area. An overview on transesterification of natural oils and fats is presented which includes the following topics: Catalytic and non-catalytic reactions and their optimum reaction conditions; types of catalysts and alcoholysis; reaction kinetics and mass transfer. The reports and findings from these aspects collectively provide useful information and serve as good guidelines for transesterification research.